Ectopic thyroid tissue: anatomical, clinical, and surgical implications of a rare entity - Noussios, George; Anagnostis, Panagiotis; Goulis, Dimitrios G; Lappas, Dimitrios; Natsis, Konstantinos (European journal of endocrinology, 2011)
Ectopic thyroid tissue is a rare entity resulting from developmental defects at early stages of thyroid gland embryogenesis, during its passage from the floor of the primitive foregut to its final pre-tracheal position. It is frequently found around the course of the thyroglossal duct or laterally in the neck, as well as in distant places such as the mediastinum and the subdiaphragmatic organs. Although most cases are asymptomatic, symptoms related to tumor size and its relationship with surrounding tissues may also appear. Any disease affecting the thyroid gland may also involve the ectopic thyroid, including malignancy. The clinician must distinguish between ectopic thyroid and metastatic deposits emerging from an orthotopic gland, as well as other benign or malignant masses. Thyroid scintigraphy plays the most important role in diagnosing ectopy, but ultrasonography contributes as well. In cases of symptomatic disease, surgery is the treatment of choice, followed by radioiodine ablation and levothyroxine suppression therapy in more refractory cases. This review provides current understanding about the wide clinical spectrum of this rare condition, also referring to optimal diagnostic approach, differential diagnosis, and management strategies.